Global Burden of Sugar-Related Dental Diseases in 168 Countries and Corresponding Health Care Costs. (July 2017) - Meier, T.; Deumelandt, P.; Christen, O.; Stangl, G.I.; Riedel, K.; Langer, M.
Oral diseases such as dental caries, edentulism (tooth loss), periodontal disease (PD), and oral cancer currently constitute an increased major public health burden across the globe, with significant differences between countries. One of the main drivers of caries, edentulism, and PD is the excessive intake of sugars. Here, we aimed to quantify the global sugar-related dental health and cost burden in the year 2010. This study used a health-econometrical model to calculate the disease burden as well as the direct and indirect costs attributable to the intake of free sugars (mono- and disaccharides [MDS]). To this end, several databases from the Institute for Health Metrics and Evaluation (IHME), Organisation for Economic Co-operation and Development (OECD), Food and Agriculture Organization (FAO), and World Bank were used. In total, the corresponding disease burden in 168 countries and economic burden in 31 OECD countries were quantified. In 2010, the consumption of MDS was associated with a global dental disease burden of 4.1 million disability-adjusted life years (DALYs; 95% uncertainty interval [UI]: 2.1 to 7.4 million DALYs), with 2.7 million DALYs from MDS-related caries and 1.4 million DALYs from PD. In terms of economic costs, MDS-related dental diseases were associated with a global financial burden of 172 billion US dollars (USD; 95% UI: 91 to 295 billion USD), the largest share of which (151 billion USD) was incurred in OECD countries. Overall, 26.3% (95% UI: 13.3% to 47.5%) of the total global oral disease burden was attributed to the consumption of MDS. The present study emphasizes the need to further address the role of free sugars in oral health and nutrition policy. Although the largest share of the economic burden was accounted for by OECD countries, emerging economies should address this challenge early on in national public health policies if they are to avoid disease and the prospect of increased cost burdens.